The relationship between individual internal factors and the prevention of obesity in students of junior secondary education level (Grades 7-9) - Joyrod, Supranee; Songthap, Archin (Nurture, 2024)
Purpose: Obesity is a risk factor for non-communicable diseases in children contributing to their physical, mental and social effects. This study aimed to investigate the relationship between individual internal factors and the prevention of obesity in students at the junior secondary education level. Design/Methodology/Approach: A multi-stage random selection method was used to select 273 junior secondary education level (grades 7-9) students from the province of Chachoengsao to participate as the study’s sample. A questionnaire was used for data collection and was divided into 7 parts: (1) general information about the sample, (2) knowledge about the prevention of obesity, (3) attitudes towards the prevention of obesity, (4) motivation in obesity prevention, (5) habits in obesity prevention, (6) student allowance management and (7) obesity prevention behavior. The data were analyzed using frequency, percentage and correlation analysis. Findings: Factors correlated with obesity prevention behavior were obesity prevention habits (r=0.382) and student allowance (r=0.294). Conclusion: Parents and schools should give importance to building obesity prevention habits and encourage children to manage their allowance efficiently to be able to help prevent obesity in students at the junior secondary education level. The results from the research can be used to create a model for modifying dietary habits accordingly. The emphasis is placed on involving children in the selection of nutritious foods. Cooking substantial meals or snacks will help to develop healthy eating habits gradually. Add exercise in the form of sports games. In addition, teaching children to record their daily income and expenses for food and snacks will help them use their daily money to their full potential and build habits and values.